Political change and electoral coalitions in Western democracies - Hall, Peter A. 1950-; Evans, Georgina 1977-; Kim, Sung In (Cambridge University Press, 2023)
This text documents long-term changes in the political attitudes of occupational groups, shifts in the salience of economic and cultural issues, and the movement of political parties in the electoral space from 1990 to 2018 in eight Western democracies
Also issued in print: 2023. - Includes bibliographical references
Keywords: Geschichte 1990-2018; Political campaigns / Western countries / Case studies; Elections / Western countries / Case studies; Political parties / Western countries; Democracy / Western countries; Politische Einstellung; Wahlbündnis; Partei; Demokratie; Wahlkampf; Western countries / Politics and government; Westliche Welt